2001
DOI: 10.1021/jo010166y
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Friedel−Crafts-Type Reactions Involving N-Acyliminium Ions Derived from Glycine Templates

Abstract: Enantiomerically pure 4-substituted 2-aralkyl-2,4-dihydro-1H-pyrazino[2,1-b]quinazoline-3,6-diones (1b-m) in which the alkyl chain is (CH(2))(n), n = 1-3, behave as glycine templates giving by treatment with [hydroxy(tosyloxy)iodo]benzene in ethyl acetate cis-1-tosyloxy derivatives. When these compounds contain electron-rich aryl substituents with n = 2, they spontaneously cyclize through intramolecular Friedel-Crafts-type diastereoselective reactions to give penta- or hexacyclic compounds. Otherwise, they giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…To this effect, our investigations revealed several crucial factors in minimizing racemization especially in steps (a) and (c). The use of buffered Meerwein condition is precedented in the literature, particularly in the context of chiral substrates . We also observed that buffered Meerwein conditions can help limit racemization during the imidate formation step (a), specifically by employing a mild base additive (Na 2 CO 3 proved optimal) in conjunction with freshly prepared Meerwein reagent (Et 3 OBF 4 ) .…”
Section: Resultsmentioning
confidence: 84%
“…To this effect, our investigations revealed several crucial factors in minimizing racemization especially in steps (a) and (c). The use of buffered Meerwein condition is precedented in the literature, particularly in the context of chiral substrates . We also observed that buffered Meerwein conditions can help limit racemization during the imidate formation step (a), specifically by employing a mild base additive (Na 2 CO 3 proved optimal) in conjunction with freshly prepared Meerwein reagent (Et 3 OBF 4 ) .…”
Section: Resultsmentioning
confidence: 84%
“…A large number of research papers dealing with the synthetic application of HTIB and other similar sulfonates such as mesylate and nosylate have been published in the last five years. The functionalization of carbonyl compounds at an α-carbon represents the most typical reaction of [hydroxy(organosulfonyloxy)iodo]arenes. HTIB was recently used for the functionalization of the azabicyclic alkaloid anatoxin-a, which is one of the most potent nicotinic antagonists. Reaction of N -Boc anatoxin-a 230 with HTIB is the method of choice for the preparation of the synthetically versatile α-tosyloxy ketone 231 (eq 101) …”
Section: [Hydroxy(tosyloxy)iodo]benzenementioning
confidence: 99%
“…232 Pyrazino[2,1-b]quinazoline-3,6-dione 241 can be selectively converted into a cis-tosylate 242 by treatment with HTIB in ethyl acetate (eq 106). [233][234][235] This reaction was used as the key step in the synthesis of the didehydro analogues of N-acetylardeemin, which is an important fungal metabolite, one of the most potent known inhibitors of multidrug resistance to antitumor agents. 235 HTIB has been used in various oxidative rearrangements and fragmentations.…”
Section: [Hydroxy(tosyloxy)iodo]benzenementioning
confidence: 99%
“…This species is also generated in acid from the hydroxy derivative 182 and it can be trapped by O-or C-nucleophiles to give aducts 183 and 184 [107] (Scheme 37). Application of this methodology to adequate N-arylalkyl substituted compounds such as 185 permits intramolecular cyclizations through tosyloxy and acyliminium intermediates 186 and 187 [108,109] (Scheme 38).…”
Section: Application Of N-acyliminium Ions To the Synthesis Of Pirazimentioning
confidence: 99%